ECO-INNOVATIVE ACADEMIA: UNIVERSITY BUSINESS INCUBATORS AS ENGINES FOR SUSTAINABILITY IN IRAQ - Al-Hassan, Faris Ali; Saleh, Layla Mohammed (Research Journal of Economics and Sustainable Development, 2024)
This paper explores the use of university business incubators as a strategy to improve the sustainability and performance of colleges in higher education. The study focuses on an exploratory analysis conducted at Al-Kunooz University College in Basra, Iraq. Business incubators are defined as organizations that provide newly established companies with physical space, administrative assistance, access to finance, and other support services to help them survive and grow during the first few years of operation. The research aimed to explore the possibility of adopting university business incubators and their expected implications for improving the college's sustainability. The study found that the implementation of the incubation program strategy has a statistically significant impact on achieving the sustainability of the college. The research concludes that business incubators play a crucial role in supporting sustainable business entrepreneurship, contributing to developing small business organizations, and promoting economic development strategies. The findings suggest that universities should consider adopting incubation programs as a strategy to improve the sustainability and performance of colleges. The study provides valuable insights into the potential benefits of incubation programs and their impact on college sustainability.